Acute effect of fructose on postprandial lipaemia in diabetic and non-diabetic subjects. - Abraha, A; Humphreys, S; Clark, M; Matthews, DR; Frayn, K (1998)
We investigated whether the potentiation of postprandial lipaemia by fructose occurs in both non-diabetic subjects and those with non-insulin-dependent diabetes mellitus. Six non-diabetic and six diabetic subjects were studied on two occasions. They were given a meal containing 1 g fat/kg body weight with, on one occasion, 0.75 g fructose/kg body weight, on the other occasion 0.75 g starch/kg body weight. In both groups, plasma glucose and insulin concentrations rose more after starch than after fructose. At 1-2 h after the meal, plasma non-esterified fatty acid concentrations were suppressed more after fructose than after starch, but later they rose more after fructose than after starch. Plasma triacylglycerol concentrations rose more slowly after fructose, but were considerably higher than those after starch from 4-6 h after the meal. There were no differences in post-heparin plasma lipoprotein lipase (EC 3.1.1.34) activity at the end of the test. The potentiation of postprandial lipaemia by fructose was positively related to the fasting plasma insulin concentration, suggesting that insulin-resistant subjects are more prone to this effect. We conclude that the potentiation of postprandial lipaemia by fructose is seen in both diabetic and non-diabetic subjects. Our results suggest that alterations in the dynamics of plasma non-esterified fatty acids might underlie the effects of fructose on triacylglycerol metabolism.